EXAMINING THE LIVER ENZYMES IN NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD) PATIENTS: A CROSS-SECTIONAL STUDY. - Alam, Md Sharfe; Iqubal, Md. Arif; Choudhary, Sangita; Rahman, Md. Faizur (Student’s Journal of Health Research Africa, 2024)
Background: Up to the present, the detection of non-alcoholic fatty liver disease (NAFLD) is done using biopsy. The exploration of a painless substitute, such as biomarkers, is a rationale for investigation. Earlier research has evaluated that patients with diabetes or overweight do not affect liver enzymes causing chronic liver problems. The goal of this research is to examine the liver enzymes in the case of NAFLD. Materials and Methods: This is cross-sectional research in which 80 subjects were included which was carried out at Katihar Medical College in Katihar, Bihar, India. Patients were divided into four categories according to their BMI, category 1 (obese), category 2 (type 1 obesity), category 3 (type 2 obesity), and category 4 (type 3 obesity), excluding the patients who have hepatitis and consume alcohol. Results: Most of the patients had type 2 obesity in which 18 males and 13 females were present. 7 male and 12 female patients had type 1 obesity. Male patients were 48 and female patients were 32The disease was prevalent in both genders. Conclusion: In the present study, it was concluded that there are variations in liver enzymes and the significance of sex, body weight, and dysfunction in lipid profile to examine the threat of patients with non-alcoholic fatty liver disease. Recommendation: Biopsy is the best mode for the detection of NAFLD and other ultrasound such as an MRI scan or CT scan can also be done for the diagnosis of hepatic dysfunction.